Developing rural school leaders : building capacity through transformative leadership coaching - Klar, Hans W.; Huggins, Kristin Shawn (Routledge, 2020)
Developing Rural School Leaders combines a focus on rural education and school leadership development to illustrate how the teaching and learning conditions in rural schools can be enhanced through transformative leadership coaching. By unpacking literature related to rural school leadership development and using case studies to authentically illustrate the complexities involved in rural school leadership development, this book explores how leaders can develop their abilities to increase data-informed instructional decision making, create a culture that supports teaching and learning, and develop other leaders. Ultimately, this important book concludes with an exploration of the opportunities and challenges of developing rural school leaders.